14. ASSESSMENT OF RIGHT VENTRICULAR FUNCTION BY ECHOCARDIOGRAPHY IN PATIENTS AFTER HEART TRANSPLANTATION OVER 3 YEARS AT VIET DUC HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate right ventricular function by echocardiography in patients after heart transplantation for more than 3 years at Viet Duc Friendship Hospital.Research subjects and methods: A retrospective and cross-sectional descriptive study on 28 patients undergoing heart transplantation at Viet Duc Friendship Hospital was conducted from August 2023 to September 2024. The study surveyed general information of patients, medical history and risk factors before heart transplantation, post-transplant diseases, and ultrasound characteristics of right ventricular function, including: 1) size assessment index, 2) overall function assessment index, 3) right ventricular systolic function assessment index, ventricular diastolic function index, 4) Right ventricular myocardial strain index.Results: The rates of total right ventricular dysfunction, systolic dysfunction, diastolic dysfunction, and strain dysfunction after 3 years of heart transplantation in the study were 28.6%, 10.7%, 10.7%, and 32.1%, respectively.Conclusion: It is necessary to periodically monitor and evaluate patients after heart transplantation by ultrasound to detect cardiac dysfunction in general and right ventricular dysfunction in particular.
Keywords: right ventricular function; heart transplantation; after 3 years; right ventricular dysfunction